Evaluation of patients who underwent invasive mechanical ventilation in a pediatric intensive care unit: a prospective study - Sıdıka Canan Atasoy; Rıza Dinçer Yıldızdaş; Özden Özgür Horoz; Ergin Atasoy; Faruk Ekinci; Sinem Sarı Gökay; İlknur Tolunay (Scientific Reports in Medicine, 2026)
Objective: To evaluate the use of invasive mechanical ventilation (MV) during a one-year period (2015–2016) in a pediatric intensive care unit (PICU), identify the most common complications and mortality rates, and compare study-period practices with more recent evidence to characterize changes in pediatric MV management over the past decade. Method: Among 781 patients followed in the PICU of Çukurova University Faculty of Medicine between February 2015 and February 2016, 173 patients who underwent invasive MV were prospectively included. Demographic data, primary diagnoses, MV indications, PICU severity scores (Pediatric Index of Mortality [PIM II], Pediatric Risk of Mortality [PRISM III], and Pediatric Logistic Organ Dysfunction [PELOD]), ventilation modes and parameters, tracheostomy status, sedation-analgesia use, weaning, complications, and ventilator-associated pneumonia (VAP) rates were analyzed. Results: Patient ages ranged from 2 months to 18 years (median 42 months, min-max 2-216); 57.2% were male. MV incidence was 22.1%. Neurological disease was the most common underlying condition (44.5%). Median PICU stay was 7 days (min-max 1-65) and median MV duration was 5 days (min-max 1-61). Complications occurred in 20.2% of patients; atelectasis (7.5%), VAP (6.9%), and pneumothorax (5.2%) were most frequent. VAP rate was 4.46/1,000 ventilator days. Tracheostomy was performed in 37 patients (21.4%). Mortality rate was 11%. Conclusion: MV practices in the PICU were largely consistent with international standards. Ventilator parameters were broadly maintained within lung-protective ranges across the cohort; together with a VAP prevention bundle, this may have contributed to the comparatively low complication rate.